Volvulus of the Small Bowel Due to Malrotation During Pregnancy: A Case-Report - E Constanthin Paul; Darouichi M. (Journal of Digestive Disorders And Diagnosis, 2017)
Volvulus occurring during pregnancy is a rare complication, still potentially lethal nowadays for both the mother and child due to several, early arising complications. We report here a case of small bowel volvulus in a 28 weeks and 4 days, 29 years-old, pregnant woman with a past medical history of appendectomy in her childhood. Patient presented in emergency department with abdominal pain and abnormal hepatic tests. Cholangio-MRI suggested bowel obstruction due to volvulus that was confirmed by gastroscopy (showing the obstruction) and intestinal MRI. Patient was first treated by laparoscopy but, due to a very complicated abdominal status with the presence of several adhesions of the small bowel, surgery was changed to an open laparotomy, which allowed discovery and repositioning of small bowel malrotation and removal of adhesions. Both patient and the foetus were healthy after surgery and the patient was then discharged. In the light of this particularly rare case of small bowel volvulus due to malrotion, we will describe the pathology of bowel obstruction and more particularly volvulus during pregnancy and discuss its diagnosis and treatment.
Keywords: Small Bowel Obstruction